The effects of vanadate on the fluxes of sodium and potassium ions through the sodium pump - Beaugé, L. A. (1980)
1. The effects of sodium orthovanadate on the fluxes of sodium and potassium (or rubidium) ions through the sodium pump have been investigated in intact human red cells and in resealed ghosts prepared from them. Sodium—potassium exchange, potassium—potassium exchange, pump reversal, sodium—sodium exchange and uncoupled sodium efflux have each been studied. 2. When intact human red cells were incubated in high-sodium media containing vanadate in low concentrations, inhibition of potassium or rubidium influx was marked only if the potassium or rubidium concentration in the medium was sufficiently high to cause nearly maximal influx in the absence of vanadate. The absence of inhibition at lower potassium or rubidium concentrations cannot be explained by supposing that the onset of inhibition by vanadate is slower in these conditions. 3. Lowering the extracellular sodium concentration, or raising the vanadate concentration, decreased the minimum concentration of extracellular potassium or rubidium at which inhibition by vanadate was detected. 4. Experiments on potassium influx into intact red cells treated with the ionophore A23187 showed that magnesium ions act at intracellular sites to promote inhibition by vanadate. 5. Measurements of potassium efflux from intact red cells incubated in high-sodium media, with or without potassium, showed that potassium—potassium exchange was inhibited by vanadate at low concentrations whereas reversal of the pump was not. 6. Measurements of sodium efflux from intact red cells or resealed ghosts incubated in high-sodium media, with or without potassium, showed that vanadate had little or no effect on sodium—sodium exchange at concentrations at which sodium—potassium exchange was markedly reduced. Much higher concentrations of vanadate did cause partial inhibition of sodium—sodium exchange. 7. Experiments to determine whether vanadate in low concentrations inhibited uncoupled sodium efflux were inconclusive, but suggested that the flux was inhibited. Measurements of the ATP hydrolysis that is thought to be associated with the uncoupled sodium efflux showed that this hydrolysis was strongly inhibited. 8. The different effects of vanadate on the different fluxes are discussed, and related to the way in which vanadate is thought to act on the sodium pump.